2004
DOI: 10.1029/2003wr002722
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic analysis of tidal creek networks

Abstract: [1] The purpose of this study is to determine if concepts in terrestrial channel network analysis provide insight on intertidal creek network development and to present new metrics for their analysis. We delineated creek network geometry using high-resolution digital images of intertidal marsh near Georgetown, South Carolina. Analyses reveal that intertidal creek networks may be topologically random. Length-area relationships suggest that salt marsh and terrestrial networks have similar scaling properties, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…3). We computed total creekbank length using a marsh island creek density of 0.013 m/m 2 (Novakowski 2004), marsh area of 17.9 km 2 and interisland creek length of 29 km (Morris et al 2005). The resulting fluxes of 0.44 to 8.4 L/m 2 per tide bracket the prior estimate of Morris (1995; 5 L/m 2 per tide) and are somewhat lower than those of Krest et al (2000; 10 to 20 L/m 2 per tide).…”
Section: Discussionmentioning
confidence: 97%
“…3). We computed total creekbank length using a marsh island creek density of 0.013 m/m 2 (Novakowski 2004), marsh area of 17.9 km 2 and interisland creek length of 29 km (Morris et al 2005). The resulting fluxes of 0.44 to 8.4 L/m 2 per tide bracket the prior estimate of Morris (1995; 5 L/m 2 per tide) and are somewhat lower than those of Krest et al (2000; 10 to 20 L/m 2 per tide).…”
Section: Discussionmentioning
confidence: 97%
“…Rinaldo et al, 1999a;Marani et al, 2003;Novakowski et al, 2004;Vandenbruwaene et al, 2012a, b), have confirmed that tidal networks show distinctive landscapes and geometric characteristics, because of the highly complicated interactions between various processes such as waves, tides, biological activities and sea level rise. By limiting the number of active processes, controlled laboratory experiments provide an important alternative to gain insight (Stefanon et al, 2010(Stefanon et al, , 2012Vlaswinkel and Cantelli, 2011;Kleinhans et al, 2012;Iwasaki et al, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…For example, each minute of rainfall duration leads to a progressively larger swath of marsh delivering sedi ment-laden rainwater directly to the creek network. Given an intertidal creek density of 13.1 kmlkm 2 [Novakowski et al, 2004], and given an average sheet flow velocity of 2cmlsec [Mwamba and Torres, 2002], and using estimates ofOC mobilization derived from plot experiments [Torres et al, 2003J, we infer that a lO-minute long, low tide, high inten sity rainstorm (-100 mmIhr) delivers 34-60 tons of particulate OC (POe) to intertidal creeks.…”
Section: Effects Of Rainfall Mobilizationmentioning
confidence: 99%
“…Large tidal channels (~5-200 m wide) dissect the expansive, low relief salt marsh platform, and smaller tidal creeks (0.5-5 m width) etch the marsh platform, becoming "dry" at low tide. In an 8.7 km 2 area of the estuary there are 725 individual, discrete creek networks with total creek length of 114 km, giving an ave rage drainage density of 13.1 kmlkm 2 [Novakowski et at, 2004]. Detailed RTK-GPS surveys of the subtle marsh platform topography reveal-0.70m of total relief, or 2.5 m when including the smaller tidal creeks [Montane and Torres, sub mitted].…”
Section: Study Sitementioning
confidence: 99%